1975
DOI: 10.1007/bf01685332
|View full text |Cite
|
Sign up to set email alerts
|

Studies on combined effects of organophosphates and heavy metals in birds. I. Plasma and brain cholinesterase in coturnix quail fed methyl mercury and orally dosed with parathion

Abstract: We found that mercury potentiated the toxicity and biochemical effects of parathion. Male Coturnix quail (Coturnix coturnix japonica) were fed a sublethal concentration of morsodren (4 ppm as methyl mercury) for 18 weeks. This resulted in an accumulation of 21.0 ppm of mercury in the liver and 8.4 ppm in the carcass. Birds fed clean feed and those fed morsodren-treated feed were orally dosed with 2, 4, 6, 8,and 10 mg/kg parathion, and their 48-h survival times compared. The computed LD50 was 5.86mg/kg in birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Considering the potential correlation between BChE and AChE inhibition, these data could provide information on the toxicological risk to which the birds are exposed and whether the percentage inhibition of AChE exceeds the two risk levels indicated by Ludke et al (1975) and by Peakall (1992), namely, O-20% = zone of normal variation, 20-50% = presence of exposure or zone of reversible effects: 50-100% = life-threatening situation or zone of irreversible effects. This approach is supported by the data of Dieter and Ludke (1975), who demonstrated a linear relationship between dose of ChE inhibitor (Parathion) and plasma ChE inhibition, and by the recent data of Fossi et al (1993), who demonstrated a linear relationship (r = 0.8859, p < 0.0001) between AChE inhibition and BChE inhibition in the reptile Gdotiu gulloti 24 h after experimental treatment with Trichlorphon at 5 mg kg-l, 50 mg kg-' and 100 mg kg-' and by Lari et al (1993) in Coturnix coturnix juponicu after dosing with 0.5 Azinphos-methyl at 0.5 mg kg-', 5 mg kg-' and 50 mg kg-' (correlation AChE-BChE after 7 h, r = 0.901, p < 0.0001). The present results perhaps suggest that the correlation between serum and brain cholinesterases should be considered only on a short-term basis, since blood esterases recover quickly whereas brain cholinesterases remain depressed for a long period (Busby et al, 1987).…”
Section: Resultssupporting
confidence: 57%
“…Considering the potential correlation between BChE and AChE inhibition, these data could provide information on the toxicological risk to which the birds are exposed and whether the percentage inhibition of AChE exceeds the two risk levels indicated by Ludke et al (1975) and by Peakall (1992), namely, O-20% = zone of normal variation, 20-50% = presence of exposure or zone of reversible effects: 50-100% = life-threatening situation or zone of irreversible effects. This approach is supported by the data of Dieter and Ludke (1975), who demonstrated a linear relationship between dose of ChE inhibitor (Parathion) and plasma ChE inhibition, and by the recent data of Fossi et al (1993), who demonstrated a linear relationship (r = 0.8859, p < 0.0001) between AChE inhibition and BChE inhibition in the reptile Gdotiu gulloti 24 h after experimental treatment with Trichlorphon at 5 mg kg-l, 50 mg kg-' and 100 mg kg-' and by Lari et al (1993) in Coturnix coturnix juponicu after dosing with 0.5 Azinphos-methyl at 0.5 mg kg-', 5 mg kg-' and 50 mg kg-' (correlation AChE-BChE after 7 h, r = 0.901, p < 0.0001). The present results perhaps suggest that the correlation between serum and brain cholinesterases should be considered only on a short-term basis, since blood esterases recover quickly whereas brain cholinesterases remain depressed for a long period (Busby et al, 1987).…”
Section: Resultssupporting
confidence: 57%
“…The whole brain was homogenized in tris buffer (35 mh/ml), pH 7.4 and stored in -20°C. The brain cholinesterase activity was determined in accordance with the method of Ellman et al (1961) as modified by Dieter and Ludke (1975). Plasma cholinesterase activity was determined following the calorimetric method of Ellman et al (1961).…”
Section: Methodsmentioning
confidence: 99%
“…According to Bakir et al (19), 5 µg/ml of mercury in the blood causes 28% of deaths in humans. All ani-mals (N = 7) were followed for 120 min and LV and RV pressures and ECG were recorded before (control condition -C) and at 1,3,5,10,15,20,30,40,50,60,70,80,90, 100, 110 and 120 min after HgCl 2 administration. Similar protocols were repeated in control animals (N = 5) without HgCl 2 injection.…”
Section: Experimental Protocolsmentioning
confidence: 99%